The effect of total cholesterol/high-density lipoprotein cholesterol ratio on mortality risk in the general population - Zhou, Dan; Liu, Xiaocong; Lo, Kenneth; Huang, Yuqing; Feng, Yingqing (Frontiers in Endocrinology, 2022)
Background: The relationship between the level of total cholesterol to high-density lipoprotein cholesterol (TC/HDL-C) ratio and all‑cause and cardiovascular mortality has not been elucidated. Herein, we intend to probe the effect of TC/HDL-C ratio on all-cause, cardiovascular mortality in general population. Methods: From the 1999–2014 National Health and Nutrition Examination Surveys (NHANES), 32,405 health participants aged ≥18 years old were included totally. TC/HDL-C levels were divided into five groups: Q1:＜2.86, Q2: 2.86-3.46, Q3: 3.46-4.12, Q4: 4.12-5.07, Q5:＞5.07. Multivariate Cox regression models were carried out to explore the relationship between the level of TC/HDL-C ratio and cardiovascular, all-cause mortality. Two‑piecewise linear regression models and multivariate adjusted Cox restricted cubic spline regression was used to explore nonlinear and irregular shape relationships. Kaplan–Meier survival curve and subgroup analyses were conducted. Results: The population comprised 15,675 men and 16,730 women with the mean age of 43 years. During a median follow up of 98 months (8.1 years), 2,859 mortality cases were recorded. All cause mortality and cardiovascular mortality shown non-linear association after adjusting for confounding variables in the restricted cubic spline analysis. Hazard ratios (HRs) of all cause mortality was particularly positively related to level of TC/ HDL-C ratio in the higher range > 5.07, in the lower range < 2.86 (HR 1.26; 95% CI 1.10, 1.45; HR 1.18; 95% CI 1.00, 1.38, respectively). Although, the HRs of cardiovascular disease mortality shown no difference among the five groups. In two-piecewise linear regression model, a TC/HDL-C ratio range of≥4.22 was positively correlated with cardiovascular mortality (HR 1.13; 95% CI 1.02, 1.25). In subgroup analysis, A non-linear association between TC/HDL-C and all cause, cardiovascular mortality was found in the aged <65 years population, male population, the non-white population. Conclusion: A non-linear association between TC/HDL-C ratio and all-cause was found, indicated that too low or too high TC/HDL-C ratio might increase all-cause mortality, However, for cardiovascular mortality, it seems not. The cut-off value was 4.22. The individuals had higher cardiovascular mortality with TC/HDL-C ratio more than 4.22.